Childhood Obesity Declines Project: Highlights of Community Strategies and Policies - Jernigan, Jan (Child Obes, 2018)
Background: The social ecological model (SEM) is a framework for understanding the interactive effects of personal and environmental factors that determine behavior. The SEM has been used to examine childhood obesity interventions and identify factors at each level that impact behaviors. However, little is known about how those factors interact both within and across levels of the SEM. Methods: The Childhood Obesity Declines (COBD) project was exploratory, attempting to capture retrospectively policies and programs that occurred in four communities that reported small declines in childhood obesity. It also examined contextual factors that may have influenced initiatives, programs, or policies. Data collection included policy and program assessments, key informant interviews, and document reviews. These data were aggregated by the COBD project team to form a site report for each community (available at www.nccor.org/projects/obesity-declines). These reports were used to develop site summaries that illustrate how policies, programs, and activities worked to address childhood obesity in each study site. Results/Conclusions: Site summaries for Anchorage, AK; Granville County, NC; Philadelphia, PA; and New York City, NY, describe those policies and programs implemented across the levels of the SEM to address childhood obesity and examine interactions both across and within levels of the model to better understand what factors appear important for implementation success.